Effectiveness The Use Of The Question And Answer Method Through The Media Of Pictures To Increase Students' Understanding Of Arabic Vocabulary - Khairul Adam; Al-baihaqi Anas (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The researchers found problems in grade 5 at SD Jam'iiyatul Hujjaj Bukittinggi, namely students' difficulties in understanding Arabic vocabulary. To increase students' understanding of Arabic vocabulary, the researcher applied the question-and-answer method through picture media. The purpose of this study is to determine the effectiveness of using the question and answer method through picture media to increase Arabic vocabulary and to find out the increase in Arabic vocabulary mastery after using the question and answer method through picture media at SD Jam'iiyatul Hujjaj Bukittinggi.This study used quantitative research with a group pretest-posttest design. Researchers took samples in this research experimental class of 28 students and control class of 28 students.The tools used for collecting data were observation, examination, and documentation. and student learning outcomes using the question-and-answer method through media images of 5th grade elementary school students. Based on the acquisition of an average value of 83, This is also proven through the calculation of "T." Calculate more than the "T" Table, namely 2,463.Then H0 is rejected and Ha is accepted. So it can be concluded about the effectiveness of the use of the question and answer method through picture media for students in grade 5 at SD Jam'iiyatul Hujjaj Bukittinggi.